The shape of things photographs from Robert B. Menschel - Bajac, Quentin 1965- (The Museum of Modern Art, 2016)
"This survey explores 60 remarkable photographs from the collection of The Museum of Modern Art, all acquired with the support of Robert B. Menschel and meticulously selected for the book by the museum's chief curator of photography, Quentin Bajac. Ranging from the contemporary artist Andreas Gursky to William Henry Fox Talbot, one of the medium's founding figures, these works collectively tell the story of photography from its beginnings, but upend and newly illuminate that story through their arrangement in reverse chronological order. Each image is the subject of a brief, elegant text. The book borrows its title from a work by Carrie Mae Weems, one of the many great photographs that Menschel has contributed to the collection."
Published in conjunction with the exhibition "The shape of things: photographs from Robert B. Menschel" at The Museum of Modern Art, New York, October 29, 2016-May 7, 2017
Includes bibliographical references (pages 146-149) and index
Keywords: Menschel, Robert B.; Museum of Modern Art (New York, N.Y.) / Exhibitions; Museum of Modern Art -- New York, NY -- Department of Photography; Geschichte 1900-2000; Photography / History / 20th century / Exhibitions; Geschichte; Sammlung; Fotografie; Ausstellungskatalog -- The Museum of Modern Art -- 29.10.2016-07.05.2017 -- New York, NY; Bildband